Informal economy in coffee country: farmers’ use of Western certification schemes - Schaltz, Theresa Sønderskov; Bork, Frederikke Korsgaard (Diálogos Latinoamericanos, 2019)
This article investigates formal and informal economies in the Colombian coffee industry. We look at the United Nations’ Sustainable Development Goals (SDGs), specifically goal no. 12 on Responsible Consumption and Production. One way of formalising is through the use of certifications. The article is based on fieldwork in Colombia, interviews with roasters and online research. We investigate the use of certifications as a way to ensure fair trade, natural resources and sustainable livelihoods, and look critically at certification programmes, and how certificates can be problematic for producers. Further, we look at direct trade as an alternative to established certification programmes. We look at direct trade, not as a replacement for formalized certification programmes, but as an alternative for some coffee producers, and we argue that there are several ways to include the United Nations’ SDG no. 12 into the coffee industry.